INTRODUCING STEAM TECHNOLOGIES INTO THE RUSSIAN LANGUAGE EDUCATIONAL PROCESS - Khalikova Gulbahor; Farangiz Salokhojaeva (Journals Park Publishing, 2022)
This article is devoted to pedagogical methods for the development of students' language competencies based on STEAM technologies in the study of the Russian language. The paper considers some ways of introducing humanitarian, natural and technical fields of science in the process of learning the Russian language.
Keywords: STEAM education; competence; Russian language